Energy Expenditure in People with Diabetes Mellitus: A Review - Caron, Nathan; Peyrot, Nicolas; Caderby, Teddy; Verkindt, Chantal; Dalleau, Georges (Frontiers in Nutrition, 2016)
Physical activity is an important non-therapeutic tool in primary prevention and treatment of diabetes mellitus (DM). To improve activity-based health management, patients need to quantify activity-related energy expenditure and the other components of total daily energy expenditure. This review explores differences between the components of total energy expenditure in patients with DM and healthy people and presents various tools for assessing the energy expenditure in subjects with DM. From this review, it appears that patients with uncontrolled DM have a higher basal energy expenditure than healthy people which must be considered in the establishment of new basal energy expenditure estimate equations. Moreover, studies showed a lower activity energy expenditure in patients with DM than in healthy ones. This difference may be partially explained by patient with DM’s poor compliance with exercise recommendations and their greater participation in lower intensity activities. These specificities of physical activity need to be taken into account in the development of adapted tools to assess activity energy expenditure and daily energy expenditure in people with DM. Few estimation tools are tested in subjects with DM and this results in a lack of accuracy especially for their particular patterns of activity. Thus, future studies should examine sensors coupling different technologies or method that is specifically designed to accurately assess energy expenditure in patients with diabetes in daily life.